Annual Variation in Northern Bobwhite Survival and Raptor Migration - R. Douglas Holt; L. Wes Burger Jr.; Bruce D. Leopold; K. David Godwin (National Quail Symposium Proceedings, 2017)
We estimated survival of radio-marked northern bobwhite (Colinus virginianus) on a managed prairie site in northeast Mississippi during 2 disparate winters (15 Sep-14 Apr 2000–2002). We retrospectively examined factors that may influence bobwhite survival. Pooled survival rates differed substantially between years (S 1⁄4 0.03 6 0.02 in 2000–2001 and S 1⁄4 0.36 6 0.16 in 2001–2002). Regional relative abundance of 3 species of raptors thought to be important predators of bobwhite was greater during 2000 compared to 2001 based on kriging of Christmas Bird Count (CBC) data. We demonstrate an approach for characterizing annual variation in spatial distribution of migratory raptors and suggest that annual variation in local winter predator context may be useful for explaining annual variation in winter survival of local bobwhite populations.
Keywords: Colinus virginianus; Mississippi; northern bobwhite; predation; raptors; Survival